Influence of personality profile in patients with drug‐resistant epilepsy on quality of life following surgical treatment: A 1‐year follow‐up study. (22nd August 2022) - Iurina, Elena; Bailles, Eva; Carreño, Mar; Donaire, Antonio; Rumià, Jordi; Boget, Teresa; Bargalló, Núria; Setoain, Xavier; Roldan, Pedro; Conde‐Blanco, Estefanía; Centeno, María; Pintor, Luis
Abstract: The objectives of this study are to determine the influence of personality profile in patients with drug‐resistant epilepsy on quality of life (QoL) after surgical treatment and compare the results with a non‐surgical control group at the 1‐year follow‐up. We conducted a prospective, comparative, controlled study, including 70 patients suffering from drug‐resistant epilepsy. Demographic, psychiatric, neurological, and psychological data were recorded at the baseline and at the 1‐year follow‐up. Assessment of personality dimensions was performed using the NEO‐FFI‐R questionnaire; severity of anxiety and depression were assessed by the Hospital Anxiety and Depression Scale (HADS), and QoL was evaluated using the QOLIE‐31. At the 1‐year follow‐up, comparing the control and the surgical groups, we detected differences in scores of most items of QoL, which were higher in those patients who had undergone surgery. High levels of Conscientiousness and Openness to experience at the baseline in patients who underwent surgery predicted better post‐surgical outcomes in the QoL scores, whereas high neurotic patients showed worse QoL results. Postoperative changes in QoL in patients were associated with the personality profile at the baseline. QoL measures significantly improved in the surgical group compared with the non‐surgical group but were not associated with baseline or postoperative seizure frequency at 1 year.